Europe's semiconductor makers are back in the game. - Blau, J. (IEEE spectrum)
European chipmakers have bounced back after being declared nearly dead almost two decades ago - and despite one of the worst downturns in the global semiconductor industry. Three of the world's top 10 chipmakers are now European, compared with just one a decade ago, according to IC Insights Inc., a market research group (Scottsdale, Ariz.). The French-Italian venture STMicroelectronics NV (Geneva) is ranked fourth. Germany's Infineon Technologies AG (Munich), despite its dependence on the ravaged DRAM and telecom markets, claims sixth place. Royal Philips Electronics NV (Amsterdam) is tenth. Europe has shown a remarkable determination to retain control of enabling technology in integrated circuits and become competitive in this market. Its technology leaders have pushed through major restructuring, from consolidation to cooperation. Equally important, they have found not only new ways to manufacture chips but also new uses beyond computers. Introducing 300-mm wafers has been one of several reasons for the renewed success.